2000
DOI: 10.1103/physreve.62.5948
|View full text |Cite
|
Sign up to set email alerts
|

Percolation parameter and percolation-threshold estimates for three-dimensional random ellipses with widely scattered distributions of eccentricity and size

Abstract: In fractured materials of very low matrix permeability, fracture connectivity is the first-order determinant of the occurrence of flow. For systems having a narrow distribution of object sizes (short-range percolation), a first-order percolation criterion is given by the total excluded volume which is almost constant at threshold. In the case of fractured media, recent observations have demonstrated that the fracture-length distribution is extremely large. Because of this widely scattered fracture-length distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
3
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(85 citation statements)
references
References 16 publications
2
78
3
2
Order By: Relevance
“…Then, a complexity such as variable apertures, spatially correlated fractures, and porous matrix was added. de Dreuzy et al (2000) studied the influence of lognormal distributed apertures on K eqv of the two-dimensional power law distributed fracture networks, and they found that a power law still governs the relation between K eqv and p but the effect of aperture distribution is dependent on the power law size exponent and the correlation between the fracture size and aperture. de Dreuzy et al (2004) shows using the numerical results with two-dimensional hypothetical fracture networks that the more spatially correlated fracture network has the less equivalent permeability although the broader fracture size distributed network the larger equivalent permeability.…”
Section: Introductionmentioning
confidence: 98%
“…Then, a complexity such as variable apertures, spatially correlated fractures, and porous matrix was added. de Dreuzy et al (2000) studied the influence of lognormal distributed apertures on K eqv of the two-dimensional power law distributed fracture networks, and they found that a power law still governs the relation between K eqv and p but the effect of aperture distribution is dependent on the power law size exponent and the correlation between the fracture size and aperture. de Dreuzy et al (2004) shows using the numerical results with two-dimensional hypothetical fracture networks that the more spatially correlated fracture network has the less equivalent permeability although the broader fracture size distributed network the larger equivalent permeability.…”
Section: Introductionmentioning
confidence: 98%
“…The fracture length distribution is a critical parameter in controlling connectivity and permeability [23,24]. Observations of fracture traces in outcrops show that fracture lengths follow power-laws [25,26].…”
Section: Poissonian Dfn Modelmentioning
confidence: 99%
“…In Figure 1, we present a very complex discrete fracture network (F N) [5,4,9]. This network contains difficult configurations that complicate the generation of the fractures' mesh (to simplify the notation, a mesh of a network means a triangulation).…”
Section: Fig 2 Flow Fluid Simulation In Capillary Network Modelmentioning
confidence: 99%